Biometrics of wild Red-breasted Geese Branta ruficollis - Mitchell, Carl; Cranswick, Peter; Kharitonov, Sergei; Mitev, Daniel; Quinn, John L.; Rozenfeld, Sonia; Swann, Bob; Vangeluwe, Didier (Wildfowl, 2015)
Biometrics were taken from 242 Red-breasted Geese Branta ruficollis caught inÂ summer on the Taimyr, Yamal and Gydan Peninsulas, arctic Russia in 1996 andÂ 2007â€“2014, and from 94 birds during four catches on the wintering grounds inÂ Bulgaria in 2011â€“2014. These biometrics represent the first published data of bodyÂ measurements, flat wing lengths and mass for Red-breasted Geese using sample sizesÂ of more than 14 birds. Males were larger than females amongst adults and first-winterÂ birds. Adult male body mass was lower in winter than during moult, whereas femalesÂ showed no significant difference. In common with some other arctic-moulting gooseÂ species, the mass of most adult geese remained constant throughout the flightlessÂ moult period; however, the mass of non-breeding adult females declined. An indexÂ of adult winter flat wing length x body mass was a 100% accurate predictor of sexÂ determined by cloacal eversion (n = 22), but was less successful in determining theÂ sex of first-winter birds (92â€“93%, n = 27).